Stars and Spikes: Analyzing Fan Attraction to Star Players in the Philippine Professional Volleyball League - Kho, Edward; Mallari, Marla Frances (Journal of Interdisciplinary Perspectives, 2024)
The study sought to describe fan consumption patterns in volleyball, identify factors influencing fan engagement, pinpoint attractive attributes of volleyball players, and compare influences on fanhood across demographic groups. The research was conducted in Pasig City, focusing on a geographically delimited non-probability sample. Data was collected through in situ surveys using questionnaires to obtain participants’ demographic profile and their motivations, preferences, and consumption patterns as league fans during match days, specifically during the last preliminary round of the league’s conference in the third week of April, with particular emphasis on the timing of visits across different days of the week. Two hundred fifty respondents participated in the survey, comprising both genders ranging in age from 10 to 78 years. Results reveal that participants identify as avid league fans and consider having a favorite league player as “definitely important” in connection with their fanhood. As to the traits of star players that attract them, 11 attributes are figured highly: passionate, professional, respectful, fair, approachable, humble, exciting, entertaining, winnable, articulate, and humble. The results provide contemporary insights into sports consumption motivations and attitudes of league fans, which can be instrumental in developing effective marketing strategies, enhancing spectator experience, and deepening the understanding of sports fandom among the Filipino audience.